2021
DOI: 10.1515/jpm-2020-0367
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the vaginal microbiome and potential restorative strategies on maternal health: a narrative review

Abstract: The vaginal microbiome undergoes dramatic shifts before and throughout pregnancy. Although the genetic and environmental factors that regulate the vaginal microbiome have yet to be fully elucidated, high-throughput sequencing has provided an unprecedented opportunity to interrogate the vaginal microbiome as a potential source of next-generation therapeutics. Accumulating data demonstrates that vaginal health during pregnancy includes commensal bacteria such as Lactobacillus that serve to reduce pH and prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Previous studies have reported that up to 40% of patients who failed assisted reproduction by in vitro fertilization (IVF) had an abnormal reproductive tract microbiome (Fanchin et al, 1998;Moore et al, 2000;Koedooder et al, 2019). Vaginal dysbiosis, including an elevated pH value, increased flora diversity, BV, vulvovaginal candidiasis, and trichomonal vaginitis, are recognized as risk factors for infertility (Campisciano et al, 2017;Moumne et al, 2021). Campisciano et al reported that the abundance of L. iners was associated with an increased infertility rate (Campisciano et al, 2020).…”
Section: Iners and Infertilitymentioning
confidence: 99%
“…Previous studies have reported that up to 40% of patients who failed assisted reproduction by in vitro fertilization (IVF) had an abnormal reproductive tract microbiome (Fanchin et al, 1998;Moore et al, 2000;Koedooder et al, 2019). Vaginal dysbiosis, including an elevated pH value, increased flora diversity, BV, vulvovaginal candidiasis, and trichomonal vaginitis, are recognized as risk factors for infertility (Campisciano et al, 2017;Moumne et al, 2021). Campisciano et al reported that the abundance of L. iners was associated with an increased infertility rate (Campisciano et al, 2020).…”
Section: Iners and Infertilitymentioning
confidence: 99%
“…The microbiome of the reproductive tracts in both males and females contribute to maintaining homeostasis and protecting against pathogens. In females, the vaginal microbiome helps regulate pH and prevent the overgrowth of potentially harmful microorganisms, which can affect fertility and increase the risk of adverse pregnancy outcomes ( Moumne et al 2021 ). In males, the prostate and seminal microbiomes are thought to influence sperm function and reproductive success ( Farahani et al 2021 ).…”
Section: ‘Reproductive’ Microbiomesmentioning
confidence: 99%
“…Interestingly, both application routes seem to be efficacious [ 86 , 87 ]. Orally administered probiotics, also referred to as food-grade supplements consisting of live microorganisms, may provide additional beneficial effects to vaginal health via the so-called “gut–vagina axis” by balancing gut microbiota and inhibiting/preventing ascension of urogenital pathogens from the rectum to vaginal tract, as well as stimulating the gut and systemic immune system [ 88 , 89 ]. Several demonstrably effective probiotic oral supplements were developed in recent years; the majority of these were used for the treatment of gastrointestinal conditions [ 90 ].…”
Section: Substances With Lactobacilli and Probioticsmentioning
confidence: 99%